Monopoli Elektronik (ME 3in1) Untuk Pembelajaran Di Sekolah Dasar Negeri Bandung Sejo Sari 3 Malang - Prathiwi Triyana; Yuninda Dewi Agustin; Inge Lailati; Nuri Yuniasih (INVENTA: Jurnal Pendidikan Guru Sekolah Dasar, 2019)
This study aims to determine the effect of Electronic Monopoly (ME 3IN1) on the learning outcomes of4th grade students at SDN Bandungrejosari 3. The approach used is quantitative research, with thetype of quasi-experimental research. The IVA study sample was 27 students (control) and IVB classtotaling 27 students (experimental). The research instrument used tests in the form of pre-test andpost-test. based on the results of the study obtained a significance value of 0.00 <0.05 so that Ho wasrejected Ha was accepted meaning that there was an influence of Electronic Monopoly (ME 3IN1) onstudent learning outcomes.